2002
DOI: 10.1128/cdli.9.2.251-256.2002
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell-Mediated Immune Responses in Patients with Cutaneous or Mucosal Leishmaniasis: Long-Term Evaluation after Therapy

Abstract: T-cell immune responses in patients with cutaneous leishmaniasis (CL) and mucosal leishmaniasis (ML)were studied during the active disease, at the end of therapy, and 1 to 17 years posttherapy (long-term follow-up). Lymphocyte proliferative responses, phenotypic characterization of CD4 ؉ and CD8 ؉ Leishmaniareactive T cells, and cytokine production were assayed. Patients with active ML and CL showed higher proportions of CD4 ؉ than CD8 ؉ T cells. In CL, the healing process was associated with a decrease of CD4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
153
3
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(176 citation statements)
references
References 33 publications
(41 reference statements)
9
153
3
9
Order By: Relevance
“…In spite of that, the MST remains positive before and after treatment, and therefore, the MST response is independent from the treatment 8 , although we cannot be certain about the changes of the MST intensity after treatment, as this has not been measured by the authors. In comparison with in vitro studies, the treatment does not change the immunological response of the patients with LCL, as demonstrated by some authors 1,13,30 . DA-CRUZ et al 13 demonstrated in peripheral blood of patients with localized cutaneous leishmaniasis caused by L. braziliensis, that the type of cytokine remains the same, i.e., the Th1 type, before and after the treatment.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…In spite of that, the MST remains positive before and after treatment, and therefore, the MST response is independent from the treatment 8 , although we cannot be certain about the changes of the MST intensity after treatment, as this has not been measured by the authors. In comparison with in vitro studies, the treatment does not change the immunological response of the patients with LCL, as demonstrated by some authors 1,13,30 . DA-CRUZ et al 13 demonstrated in peripheral blood of patients with localized cutaneous leishmaniasis caused by L. braziliensis, that the type of cytokine remains the same, i.e., the Th1 type, before and after the treatment.…”
Section: Discussionmentioning
confidence: 69%
“…In comparison with in vitro studies, the treatment does not change the immunological response of the patients with LCL, as demonstrated by some authors 1,13,30 . DA-CRUZ et al 13 demonstrated in peripheral blood of patients with localized cutaneous leishmaniasis caused by L. braziliensis, that the type of cytokine remains the same, i.e., the Th1 type, before and after the treatment. This fact supports our findings in the MST that was performed after treatment in two patients of LCL.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations